Analysis of the Quality of Arabic Language Online Test Items Based on ACTFL Standards - Mahmudi, Ihwan; Muhyiddin, Luthfi; Ismail, Moh; Saifulloh, Ahmad; Kusnawan, Wawan (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study aims to analyze the quality of Arabic language online test items at the University of Darussalam Gontor using the standards of the American Council on the Teaching of Foreign Languages (ACTFL) as a reference for item quality analysis. The item analysis was conducted on three main Arabic language skills: listening, reading, and writing. The University of Darussalam Gontor was selected as it is one of the Islamic higher education institutions in Indonesia that is committed to the development of Arabic language. This study employed a descriptive quantitative method. Data were collected through student score documents from Arabic online tests at the University of Darussalam Gontor, consisting of 20 items for the listening test, 29 for the reading test, and 29 for the writing test. The sample was selected using random sampling: 135 students for writing, 127 for listening, and 129 for reading. Data were analyzed using descriptive statistics. The results revealed that in terms of validity, the reading skill test showed the highest validity rate at 86%. In terms of reliability, the writing skill test demonstrated the highest reliability. The discrimination index analysis showed that the writing test had the best quality, while the difficulty index analysis indicated that the listening test had a fairly balanced distribution: 50% of items at a medium level, 33% easy, and 17% difficult. Furthermore, the analysis of test items based on ACTFL standards showed that items at the intermediate level still predominated.